PENGARUH PROSES BLANSING DAN SUHU PENGERINGAN PADA BUBUK CABAI MERAH BESAR (Capsicum annuum L.) DAN DAUN JERUK PURUT (Citrus hystrix) TERHADAP SIFAT SENSORI YANG DIHASILKAN THE EFFECT OF THE BLANCING PROCESS AND DRYING TEMPERATURE OF GREAT RED CHILLI POWDER (Capsicum annuum L.) AND KAFFIR LIME LEAVES (Citrus hystrix) ON THE PRODUCED SENSORY PROPERTIES - Rahmat Triharto; Suharyono -; Erdi Suroso; Tanto Utomo (Jurusan Teknologi Hasil Pertanian, 2024)
Large red chilies are a type of plant that has a low shelf life due to their high water content. The way to extend the shelf life is to process it into large red chili powders. The addition of kaffir lime leaves is also needed to add a distinctive aroma and thus increase the attractiveness of chili powder. The quality of a product is influenced by several factors, including the blanching process and drying temperature. The aim of this research was to determine the effect of the blanching process and drying temperature on the sensory properties preferred by panelists. This research used a randomized complete block design (RAKL) with 2 factors. The first factor was the blanching process: without blanching and blanching at 90 °C for 6 minutes. The second factor is drying temperature: oven drying at a temperature of 60 °C, oven drying at a temperature of 70 °C, oven drying at a temperature of 80 °C, oven drying at a temperature of 90 °C. This research was carried out in three repetitions. The data obtained were tested for similarity of variances using the bartlett test, analyzed for variance, and further processed with further orthogonal polynomial comparison tests at the 5% and 1% levels. In this research, the blanching process and temperature differences each had a very significant effect on chili powder production. However, there was no interaction between the blanching process and temperature differences in the production of large red chili powder and kaffir lime leaves.